Developing librarian competencies for the digital age - Coghill, Jeff; Russell, Roger G. (Medical Library Association books., 2017)
Developing Librarian Competencies for the Digital Age identifies specific digital skills needed for success, ways of developing those skills, and ways of assessing them. This book identifies the crux of what it means to a librarian in the 21st century. It is aimed at library professionals at any stage in their career in any library setting to become proactive in coping with the near constant state of change affecting all libraries and all library users in the modern era.